Whom do people trust after a violent conflict? Experimental evidence from Maluku, Indonesia - Katharina Werner (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
A long-standing - although not uncontested - view is that violent conflicts reduce average levels of trust. Other theoretical and empirical work emphasizes discriminatory effects, namely that conflicts may enhance ingroup trust and erode out-group trust. The present study combines a trust game and a questionnaire to investigate the impact of direct and indirect conflict exposure on trust between Muslim and Christian students in postconflict Maluku, Indonesia. Reduced average levels of trust are found for subjects who were indirectly exposed to the conflict. Discriminatory effects are related to direct exposure: Directly exposed subjects trust in-group members much more than out-group members. The rationale may be the following: Directly exposed subjects made negative experiences with outgroup members, but also experienced solidarity within their group during the conflict. Indirectly exposed subjects, on the other hand, heard about negative experiences of others without being sufficiently involved to have made such distinct experiences with in-group and out-group members. Unable to distinguish friend from foe, they reduce trust toward everyone.
Keywords: C93; Z12; Z13; 330; trust; conflict; direct exposure; indirect exposure; religion; discrimination